NA PASNÍKU - Siegelová, Kateřina (Vysoké učení technické v Brně. Fakulta výtvarných umění)
Tématem mojí diplomové práce Na Pasníku je čas a rozklad. Vyráběla jsem si malé domečky z přírodnin a ty umístila v lese. Předmětem práce je plynutí času. Výsledkem mojí práce je časová velkoformátová kresba. Domečky na kresbě se postupně rozpadají a mizí. Tímto vytvářím časovou kresbu.

The topic of my thesis On the Pasník a time and decomposition. I have produced small houses from natural materials and placed them in a forest. The subject of my work is to record the flow of time. The outcome of my work is time based large-formal drawing. The buildings on the drawing gradually collapse and disappear. Thus I have created the time drawing.
ON THE PASNIK
Keywords: domečky; čas; les; rozklad; kresba; houses; time; forest; decomposition; drawing